Determination of Ibuprofen, Pseudoephedrine HCl, Chlorpheniramine Maleate and Nipagen by Liquid Chromatography and Fractional Factorial Design - Asci, Buerge; Donmez, Oezlem Aksu; Bozdogan, Abduerrezzak; Sungur, Sidika (SPRINGER, 2009)
In the present work, a rapid and sensitive gradient HPLC method was developed for the analysis of a new syrup preparation containing ibuprofen, pseudoephedrine HCl, chlorpheniramine maleate and nipagen. The optimization process was carried out using 2(5-1) fractional factorial design. Five variables pH, flow rate and solvent ratios for three steps of gradient profile were regarded as factors in the optimisation. The resolution was used as analytical response. Using the optimised experimental conditions, the limits of quantitations (10 sigma/s) determined as 0.09, 0.01, 0.04 and 0.01 ppm for ibuprofen, pseudoephedrine HCl, chlorpheniramine maleate and nipagen, respectively. The obtained results indicated that this procedure could be applied for the determination of ibuprofen, pseudoephedrine hydrochloride, chlorpheniramine maleate and nipagen in syrup preparations.
Keywords: Chlorpheniramine; fractional factorial design; RP-HPLC; ibuprofen; nipagen; pseudoephedrine; Biochemistry & Molecular Biology; Chemistry